La construction du personnage dans la presse people - Marc Lits (Communication)
The main character rather than the plot is the central element that structures any narrative and allows all forms of identification, especially in mass cultural productions. The celebrity magazine, as a specific press genre, focuses its attention on public figures portrayed as fictional heroes. What was already an established practice in the world of entertainment now invades the political universe, as increasingly witnessed in celebrity magazines.